Plasmablastic neoplasm in an HIV affected individual and a brief note on its differential diagnosis - Hegde, Veda; Hallikeri, Kaveri; Anehosur, Venkatesh (Asian Journal of Medical Sciences, 2014)
HIV/AIDS predisposes an individual to a variety of malignancies. Lymphomas constitute a group of neoplasm of which are derived from the basic cells of lymphoid tissue, lymphocytes and histiocytes in any of their developmental stages. Thus these neoplasms are closely related and difficult to diagnose based on the histopathology alone. To highlight the importance of immuno-histochemistry in lesions as in the present case and the varied differential diagnosis that is useful to arrive at a diagnosis. We report a case of plasmablastic neoplasm in a young female whose HIV status became apparent only after the histopathologic diagnosis. Oral lesion was the only presenting feature. The lesion was a very aggressive lesion. Diverse differential diagnosis has been illustrated with their specific features which can be valuable to achieve a diagnosis of a particular lymphoma. Although, the histopathology reveals predominantly plasmablasts, it is still not possible to give an accurate diagnosis based on microscopy alone. Thus such lesions have to be differentiated with the help of immuno-histochemistry. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10762 Asian Journal of Medical Sciences Vol.6(3) 2015 77-80